2017
DOI: 10.1128/aem.02265-16
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Abundances of Total Vibrio spp., V. vulnificus, and V. parahaemolyticus in Clams and Oysters in North Carolina

Abstract: Filter feeding shellfish can concentrate pathogenic bacteria, including Vibrio vulnificus and Vibrio parahaemolyticus, as much as 100-fold from the overlying water. These shellfish, especially clams and oysters, are often consumed raw, providing a route of entry for concentrated doses of pathogenic bacteria into the human body. The numbers of foodborne infections with these microbes are increasing, and a better understanding of the conditions that might trigger elevated concentrations of these bacteria in seaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 34 publications
5
36
1
4
Order By: Relevance
“…Although pathogenic Vibrio strains are hazards for coastal systems (5,(8)(9)(10), most Vibrio strains are harmless (5). Vibrios are present in a great variety of aquatic environments from coastal areas to the deep sea (2,5), indicating that they occupy a wide range of environmental niches.…”
mentioning
confidence: 99%
“…Although pathogenic Vibrio strains are hazards for coastal systems (5,(8)(9)(10), most Vibrio strains are harmless (5). Vibrios are present in a great variety of aquatic environments from coastal areas to the deep sea (2,5), indicating that they occupy a wide range of environmental niches.…”
mentioning
confidence: 99%
“…in mussel homogenates (completely inactivated to nondetectable level) was obtained at a treatment of 350 and 450 MPa for 1 and 3 min (determined on both thiosulphate citrate bile salt sucrose (TCBS) and TSA agar), except for V. parahaemolyticus with a 4Á4 log reduction by a treatment of 350 MPa for 1 min (determined on TSA agar). At harvest, the density of Vibrio in shellfish is usually less than 10 3 CFU per gram but can exceed 10 3 CFU per gram during summer (Froelich et al 2017). However, under improper postharvest conditions, Vibrio can rapidly multiply to reach the density of 10 5 -10 6 cells per gram (Cook 1994;Gooch et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, they may differ in their preference of consuming wild‐caught or aquacultured oysters. However, studies on comparisons between the risk of V. parahaemolyticus infection resulting from the consumption of wild‐caught oysters and aquacultured oysters are limited (Froelich, Phippen, Fowler, Noble, & Oliver, 2017). Nevertheless, studies have shown that the culturing method affects the concentration of V. parahaemolyticus in oysters (Cole, Supan, Ramirez, & Johnson, 2015; Feinman, Farah, Bauer, & Bowen, 2018).…”
Section: Factors Affecting the Accumulation Of V Parahaemolyticus Inmentioning
confidence: 99%
“…Froelich et al. (2017) performed a study in the same location, North Carolina coast, and reported that SST was strongly correlated with the abundance of V. parahaemolyticus in oysters. A recent study by Hartwick et al.…”
Section: Factors Affecting the Accumulation Of V Parahaemolyticus Inmentioning
confidence: 99%
See 1 more Smart Citation